Exclusion from Educational Opportunity in Diversifying Rural Contexts. (24th May 2021) - Aylward, Alexandra; Barrio, Brenda; Kramarczuk Voulgarides, Catherine
Abstract: Racial/ethnic disproportionality within special education refers to the over‐ or underrepresentation of a racial/ethnic group in an educational category, program, or service in comparison to the group's proportion in the overall population. The educational equity implications of disproportionality have been discussed in multiple studies, and schools may risk receiving federal citations and sanctions in significant instances of disproportionality. However, disproportionality in special education is rarely examined within rural settings, despite demographic change leading to more racially and ethnically diverse rural schools. This article uses event history methodology to understand how changing district‐level social contextual factors are associated with the issuance of federal citations for disproportionality in special education during 2004–2005 to 2011–2012 school years among rural districts within New York. We find that among majority‐white districts, the likelihood of citation is much greater when there is a substantial increase in the number of children of color enrolled. In contrast, racial/ethnic demographic changes within more diverse rural districts, whether enrollment increases or decreases, reduce the likelihood of a citation. Also, as teacher turnover and student enrollments increase, the likelihood of citation increases. As rural communities continue to become less racially and ethnically homogenous, scholars and educators must consider the ways in which Black, Indigenous, and students of color can be appropriately supported in schools and the important variation across rural spaces.